Effect of Feeding Moringa Leaf Powder on Antioxidant Status of Early Weaned Large White Yorkshire Piglets Reared under Agro-climatic Condition of Mizoram, India - Pamei, Jianpui; Das, Hemen; Ali, M. Ayub; Lallianchunga, M. C.; Buragohain, Kuntal Kashyap; Swu, Kivitoli; Kalita, Girin; Das, Biren Kumar (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during April to September, 2024 at C.V.Sc and A.H., CAU, Aizawl, Mizoram, India to determine the effect of feeding Moringa leaf powder (MLP) on antioxidant status of early weaned Large White Yorkshire piglets. For the study, a total of 18 clinically healthy piglets weaned at 28 days were categorized as Control (C), Treatment-I (T1) and Treatment-II (T2) with 6 (six) piglets in each group. The control group was fed basal feed and T1 and T2 groups were fed basal feed with incorporation of MLP @ 1% and 2%, respectively. The trial was carried out for a period of 42 days. Blood was collected on day 28 (i.e day of weaning), day 42, day 56 and day 70 from each piglet of all groups for estimating the major antioxidant parameters. The antioxidants estimated were superoxide dismutase (SOD), catalase (CAT), malanaldehyde (MDA) and glutathione peroxidase (GPx). The activities of SOD varied from 0.75±0.013 to 2.01±0.005 IU ml-1 amongst the experimental groups, whereas activities of CAT ranged from 1.48±0.02 to 2.32±0.012 IU ml-1. The GPx activities were in the range of 231.93±0.49 to 234.01±0.018 (pg ml-1) and MDA concentration was in the range of 218.47±0.015 to 254.31±0.013 (ng ml-1). The study established that dietary inclusion of Moringa leaf powder improved the antioxidant arsenals of the weaned piglets, which in turn led to reduced weaning stress and resulted in their better growth. Further, data obtained in the study pertaining to SOD, CAT, GPx and MDA may be used as reference values for any future investigation.